Improvement of living standards of patients with chronic obstructive pulmonary disease - Igor Grygus; Mykola Maistruk (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study the effectiveness of the proposed method of physical rehabilitation on the quality of life of patients with chronic obstructive pulmonary disease (COPD). Material & Methods: 162 patients with COPD participated in the study. To determine the effectiveness of the physical rehabilitation, the approved Ukrainian version of the quality of life questionnaire of the World Health Organization. Result: patients of the main group noted a decrease in discomfort, dependence on medications, increased mobility, increased vitality, performance, ability to perform everyday tasks, reducing fatigue, improving sleep, thinking, and improving personal relationships. Conclusion: after applying the proposed program of physical rehabilitation for each patient with chronic obstructive pulmonary disease, we observed an increase in the overall quality of life and health in patients in the main group due to an increase in indicators in problem sub-spheres.